Effect of alcohol consumption on all‐cause and liver‐related mortality among HIV‐infected individuals1. Issue 5 (28th September 2016) - Canan, CE; Lau, B; McCaul, ME; Keruly, J; Moore, RD; Chander, G
Abstract : Objectives: The aim of the study was to examine the association between levels of past and current alcohol consumption and all‐cause and liver‐related mortality among people living with HIV (PLWH). Methods: A prospective cohort study of 1855 PLWH in Baltimore, MD was carried out from 2000 to 2013. We ascertained alcohol use by (1) self‐report (SR) through a computer‐assisted self interview, and (2) medical record abstraction of provider‐documented (PD) alcohol use. SR alcohol consumption was categorized as heavy (men: > 4 drinks/day or > 14 drinks/week; women: > 3 drinks/day or > 7 drinks/week), moderate (any alcohol consumption less than heavy), and none. We calculated the cumulative incidence of liver‐related mortality and fitted adjusted cause‐specific regression models to account for competing risks. Results: All‐cause and liver‐related mortality rates (MRs) were 43.0 and 7.2 per 1000 person‐years (PY), respectively. All‐cause mortality was highest among SR nondrinkers with PD recent (< 6 months) heavy drinking (MR = 85.4 deaths/1000 PY) and lowest among SR moderate drinkers with no PD history of heavy drinking (MR = 23.0 deaths/1000 PY). Compared with SR moderate drinkers with no PD history of heavy drinking, SR nondrinkers and moderate drinkers with PD recent heavy drinking had higher liver‐related mortality [hazard ratio (HR) = 7.28 and 3.52, respectively]. However, SR nondrinkers and moderate drinkers with a PD drinking history of > 6 months ago showed similar rates of liver‐related mortality (HR = 1.06 and 2.00, respectively). Conclusions: Any heavy alcohol consumption was associated with all‐cause mortality among HIV‐infected individuals, while only recent heavy consumption was associated with liver‐related mortality. Because mortality risk among nondrinkers varies substantially by drinking history, current consumption alone is insufficient to assess risk.